Synthesis of azepane and nojirimycin iminosugars: the sharpless asymmetric epoxidation of D-glucose-derived allyl alcohol and highly regioselective epoxide ring opening using sodium azide - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron-Asymmetry, 2010)
The Sharp less asymmetric epoxidation of D-glucose-derived ally! alcohol 4 afforded alpha- and beta-epoxides 5a and 5b in high stereoselectivity. The epoxide ring opening in 5a/5b was studied with different nucleophilic azido reagents, under various reaction conditions, and was found to be highly regioselective to give the preferential formation of 6-azido diol 6a/6b over 5-azido-diol 7a/7b. The 6-azido diol 6a/6b and 5-azido dial 7a/7b thus obtained were converted to the corresponding seven- and six-membered iminosugar, namely, azepane 1a/1b and 1-deoxy-nojirimycin 2a/2b. (C) 2010 Elsevier Ltd. All rights reserved.